2022
DOI: 10.1093/nar/gkab1303
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the SARS-CoV-2 ExoN (nsp14ExoN–nsp10) complex: implications for its role in viral genome stability and inhibitor identification

Abstract: The SARS-CoV-2 coronavirus is the causal agent of the current global pandemic. SARS-CoV-2 belongs to an order, Nidovirales, with very large RNA genomes. It is proposed that the fidelity of coronavirus (CoV) genome replication is aided by an RNA nuclease complex, comprising the non-structural proteins 14 and 10 (nsp14–nsp10), an attractive target for antiviral inhibition. Our results validate reports that the SARS-CoV-2 nsp14–nsp10 complex has RNase activity. Detailed functional characterization reveals nsp14–n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 51 publications
1
61
0
Order By: Relevance
“…Previous studies showed that the ExoN activity of nsp14 is strongly stimulated by nsp10 for both SARS-CoV and SARS-CoV-2 ( 32 , 34 36 ). In our crystal structure, the N-terminal residues of ExoN and those of nsp10 are wrapped around each other in a “criss-cross” arrangement and forming several hydrogen bond contacts, including one between nsp14 Lys9 and nsp10 Ala1 ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Previous studies showed that the ExoN activity of nsp14 is strongly stimulated by nsp10 for both SARS-CoV and SARS-CoV-2 ( 32 , 34 36 ). In our crystal structure, the N-terminal residues of ExoN and those of nsp10 are wrapped around each other in a “criss-cross” arrangement and forming several hydrogen bond contacts, including one between nsp14 Lys9 and nsp10 Ala1 ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Excision proceeds in single base increments as confirmed by sizing analysis performed by Baddock et al. [ 41 ], which indicates there is a nucleophilic attack of the scissile phosphodiester, and protonation of the leaving group, catalyzing a 3′–5′ nucleoside monophosphate exit. Likewise, a self‐assembled monolayer for matrix‐assisted laser desorption ionization (SAMDI) mass spectrometry assay indicates that Nsp14/Nsp10 requires a 3′OH, confirming that the enzyme acts in a 3′–5′ direction and that the first nucleotide likely is digested before proceeding with subsequent activities [ 42 ].…”
Section: Nsp14mentioning
confidence: 80%
“…[ 46 ] have shown biochemically that Nsp10/14 hydrolyzes RNAs in dsRNA, ssRNA, and RNA DNA/hybrid. Likewise, cleavage is observed on a mismatch at the 3′ end of RNA, while longer flaps or gaps showed no strong preference in exonuclease activity [ 41 ]. At high concentrations Nsp14, in the absence of Nsp10, has also been shown to minimally act on dsRNA substrates.…”
Section: Nsp14mentioning
confidence: 99%
See 1 more Smart Citation
“…The structural basis of nsp14 interaction with nsp10 has been elucidated 11 . We have recently demonstrated that nsp14, nsp10 and nsp16 form a ternary complex, further modulating nsp14 catalytic activity 12 .…”
Section: Introductionmentioning
confidence: 99%